Design and Implementation of a Distance Training Device of Physical and Sports Education’s Future Teachers : Application of ADDIE Model - HAMSE, Mostafa; Said Lotfi; Mohammed Talbi, (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2022)
Distance learning has largely infiltrated several higher education institutions in Morocco driven by the expansion of opportunities offered by information and communication technologies such as ODL, MOOC, SPOC. However, countless challenges continue to hamper the design, implementation and evaluation of these devices in education and vocational training for desired effectiveness. The aim of this study is to design an ODL system based on the SPOCs model which aims to develop professional skills for 70 future teachers of Physical and Sports Education.We have used ADDIE model as a methodological tool for our technopedagogical design with its Analysis, Design, Development, Implementation and Evaluation phases.Using Chi-square test, we examined the effect of the following independent variables: form of content, on trained type groups : hybrid and distanced at the threshold of p <.05. The results obtained show that trainee teachers have an increased need for their professional skills development through our FP@STAPS device using various digital resources. Thus, the evaluation of this device has shown its usefulness and effectiveness.The study therefore recommends the integration of this type of training into vocational training centers in Morocco. In addition, the study recommends that its technopedagogical design be based on referenced models such as ADDIE.